A method for preparing a lithium ion battery negative electrode material
Patent Information
- Application Number
- CN202611135578.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-16
AI Technical Summary
经检索,目前国内外尚未见有通过空气氛围下直接煅烧石墨与乙酰丙酮镍的混合物制备石墨/氧化镍/镍复合材料的相关研究报道
[0013] The preparation process of this invention is safe and environmentally friendly, with a simple procedure and controllable cost, making it suitable for large-scale production and promotion. The sample prepared by this invention has a yield of 0.2 A g. -1 The initial discharge specific capacity is more than 1.6 times that of commercial graphite. Especially at 5.0 A g. -1 At high current density, the discharge specific capacity after 100 cycles is 2.5 to 10.7 times that of commercial graphite batteries, and it also exhibits good cycle stability. This demonstrates that the graphite/nickel oxide/nickel material prepared in this invention is an ideal anode material for lithium-ion batteries with broad application prospects.
Smart Images

Figure CN122930871A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy materials technology, and more specifically, to a method for preparing a lithium-ion battery anode material. Background Technology
[0002] Since the beginning of the 21st century, among many energy storage devices, rechargeable lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage systems due to their advantages such as high operating voltage, long cycle life, and environmental friendliness.
[0003] Lithium-ion batteries generally consist of core components such as a positive electrode, a negative electrode, electrolyte, and separator. Among these, the negative electrode material is a key component determining the overall performance of the battery, and its selection and optimization directly affect the battery's energy density, cycle stability, and safety. Currently, commercially available lithium-ion battery negative electrode materials mainly use lithium titanate and graphite. Graphite occupies a large share of the lithium-ion battery negative electrode material market due to its abundant resources, low cost, mature manufacturing process, and excellent conductivity. Recent studies have shown that graphite negative electrodes experience rapid capacity decay and significantly reduced cycle stability at high current densities, making it difficult to meet the demands of next-generation high-energy-density batteries. Furthermore, under abnormal conditions such as overcharging, lithium dendrites are prone to precipitate on the graphite surface. Under certain conditions, these dendrites may pierce the separator, causing internal short circuits and posing a serious safety hazard. Therefore, effectively improving the electrochemical performance and safety stability of graphite negative electrode materials is one of the urgent problems to be solved in current lithium-ion battery research.
[0004] Research shows that there are currently three main methods for modifying graphite, namely (1) modification and morphology control of graphite surface. That is, to improve the electrochemical performance of graphite by changing its surface properties and morphology. For example, Tang Jingjing et al. (CN122324802A) disclosed a method for preparing modified graphite anode material. This method mainly prepares Li-Si-PSO composite phase by ball milling to pre-create defects, mixed acid etching, three-stage replacement, two-stage reaction and hydrogen reduction. This composite phase can optimize the graphite structure and significantly improve the low-temperature performance of graphite. Zhang Shuanghu et al. (CN122276740A) disclosed a method for preparing carboxyl-modified graphite. This method is to prepare porous graphite oxide and introduce carboxyl functional groups to make the graphite surface have nanopores and increased interlayer spacing. Using this material can significantly improve the wettability of graphite with electrolyte and accelerate the insertion / extraction of lithium ions, so as to improve the rate performance of graphite and accelerate the lithium ion transport kinetics. (2) Surface coating and composite. This refers to improving the electrochemical performance of graphite through carbon coating and composite with metal oxides. For example, Gao Min et al. (CN122314822A) disclosed a patent for a silicon-carbon composite material and its preparation method. This patent uses modified graphite as a matrix and embeds silicon material into the pores and surface of graphite to form a double-layer carbon-coated structure. This structure can improve the conductivity of graphite and suppress silicon volume expansion, thereby improving rate performance and cycle stability. Li Xifang et al. (CN122314757A) disclosed a method for preparing modified graphite materials. This method first borates the graphite and then uses a coating agent containing inorganic fluorine source and organic fluorine source to fluorocarbon coat the graphite. This method can improve the lithium-ion conductivity and high-temperature performance of graphite and improve the high-temperature cycle performance of the battery. Lin Ning et al. (CN122276738A) disclosed a method for preparing coated graphite. This method involves multi-gradient oxidation, glucose composite, and high-pressure carbonization to make graphene sheets radially distributed on the graphite surface, forming a novel type of coated graphite. This material can significantly improve the rate performance and structural stability of graphite. Sun Lei et al. (CN122202234A) disclosed a modified graphite. In this method, graphite is aminated and then reacted with a sulfur- and nitrogen-containing fused ring conjugated polymer to form a robust core-shell coated structure. This structure can improve the conductivity of graphite, inhibit the expansion of graphite, and improve the high rate and long cycle performance of the battery. (3) Element doping. This refers to the method of doping different elements into graphite to improve the electrochemical performance of graphite. For example, Li Zaijun et al. (CN104882608A) disclosed a method for preparing a nitrogen-doped three-dimensional graphene / graphite composite anode material. This patent believes that nitrogen doping can enhance the electrochemical reaction activity, thereby significantly improving the rate performance and cycle stability of the anode.
[0005] It is worth noting that, in addition to the aforementioned strategies for modifying graphite itself, combining metal oxides with graphite / carbon materials is also an effective way to improve the electrochemical performance of graphite. For example, Zhang Weidong et al. (CN102610809A) disclosed a method for preparing iron(III) oxide / graphite lithium-ion battery anode materials. The material prepared according to this patent showed significant improvements in cycle performance and rate performance compared to graphite. Recent studies have shown that transition metal oxides can also be used as lithium-ion battery anode materials. Nickel oxide is one of the commonly used lithium-ion battery anode materials. Yin Jingzhou et al. (CN107170983A) disclosed a method for preparing pearl cotton-like nickel oxide anode material. This method involves calcining nickel salts with glycine and isoniazid, resulting in a sheet-like hierarchical structure. This structure can alleviate the volume expansion of the material and improve the cycle performance of lithium-ion batteries. Regarding the selection of nickel sources, in addition to commonly used nickel nitrate and nickel oxalate, nickel acetylacetone can also be used as a nickel source for nickel oxide. For example, Xu Jin et al. (CN120440975A) disclosed a process for preparing high-purity nano-nickel oxide. This process uses nickel acetylacetone as a raw material and oleylamine as a soft template, and involves microwave-assisted reaction, washing, drying, and calcination. The nano-nickel oxide prepared by this process has high purity, large specific surface area, large pore volume, and small grain size. In summary, existing methods for modifying graphite anode materials often involve multi-step reactions, special atmosphere protection, or the use of expensive reagents, resulting in high process complexity and production costs, which are not conducive to industrialization. Therefore, this invention provides a simpler graphite modification strategy, requiring only a one-step calcination in air after physically mixing and grinding nickel acetylacetone with graphite to optimize the electrochemical performance of graphite. A search revealed no research reports, domestically or internationally, on the preparation of graphite / nickel oxide / nickel composite materials by directly calcining a mixture of graphite and nickel acetylacetone in air. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a graphite / nickel oxide / nickel composite material, a lithium-ion battery anode material with excellent high-rate, long-cycle performance. The preparation method involves simply physically mixing nickel acetylacetone and graphite, followed by direct calcination in air, making the process simple and efficient. Testing has shown that this material exhibits excellent performance at 5.0 A g. -1 After 100 charge-discharge cycles, the capacity is 2.5 to 10.7 times that of commercial graphite; even at 10.0 Ag... -1 After 500 cycles at high current density, the capacity remains 1.6 to 5.5 times that of commercial graphite. Compared with traditional modification techniques, this invention eliminates the need for inert atmosphere protection and complex multi-step operations, reducing preparation costs and energy consumption, making it suitable for industrial application.
[0007] Specifically, the present invention provides a method for preparing a graphite / nickel oxide / nickel composite material for lithium-ion batteries with excellent high-rate, long-cycle performance, comprising the following steps: (1) Preparation of materials Graphite; Nickel acetylacetonate (Ni(acac)2); Acetylene black; Polyvinylidene fluoride (PVDF); N-methylpyrrolidone (NMP); Celgard 2400 microporous polypropylene membrane; CR2430 button battery casing; (2) Material preparation Graphite and nickel acetylacetone were weighed out in a mass ratio of (1~2):(3~7), and the two were mixed to obtain a mixture. The mixture was then placed in a muffle furnace and calcined at 500℃~700℃ in air for 1 h~3 h to obtain a product containing graphite, nickel oxide and elemental nickel (sample name a). As a preferred condition, the mass ratio of graphite to nickel acetylacetone in step (2) is 1:5; As a preferred condition, the calcination temperature of the graphite and nickel acetylacetonate mixture in the muffle furnace in step (2) is 600°C; As a preferred condition, the calcination time of the graphite and nickel acetylacetonate mixture in the muffle furnace in step (2) is 2 hours; (3) Electrode preparation and battery assembly For comparison, the commercial graphite was named Sample O; Sample a, PVDF (polyvinylidene fluoride), and acetylene black were weighed separately and placed in an agate mortar. The mass ratio of sample a, PVDF, and acetylene black was controlled to be (8~9):(1~1.5):(1~1.5). The mixture was thoroughly ground in the agate mortar for 10~20 min. Then, N-methylpyrrolidone (NMP) was added dropwise while stirring to form a paste. The paste was then evenly coated onto a commercial copper (Cu) foil current collector. The current collector coated with the paste was then placed in a vacuum drying oven and dried at 100~140°C for 4 h~8 h. After naturally cooling to room temperature, it was removed and cut into several electrode sheets with a diameter of 1 cm using a shearing tool, thus obtaining electrode a. Replacing sample a with commercial graphite, and preparing a graphite electrode with all other conditions unchanged, is denoted as electrode o.
[0008] Using the prepared electrode a as the positive electrode, a lithium sheet as the negative electrode, a Celgard 2400 microporous polypropylene membrane as the separator, 1 mol / L LiPF6 dissolved in an organic solvent as the electrolyte, and a CR2430 button cell casing as the battery case, a half-cell was assembled in an argon-filled glove box, denoted as battery a. Electrode a was replaced with electrode o, and following the same steps, under the same conditions, a half-cell was assembled, denoted as battery o. The charge-discharge experiments of the half-cell were conducted on a high-precision battery charge-discharge tester (model CT-3008W-5V20mA-S4, Shenzhen Xinwei Electronics Co., Ltd.).
[0009] As a preferred condition, the mass ratio of sample a, PVDF and acetylene black prepared in step (3) is 8:1:1.
[0010] As a preferred condition, the grinding time for sample a, PVDF and acetylene black prepared in step (3) is 15 min.
[0011] As a preferred condition, the temperature in the vacuum drying oven during the electrode preparation process in step (3) is 120°C.
[0012] As a preferred condition, the vacuum drying time in step (3) of electrode preparation is 6 h.
[0013] The preparation process of this invention is safe and environmentally friendly, with a simple procedure and controllable cost, making it suitable for large-scale production and promotion. The sample prepared by this invention has a yield of 0.2 A g. -1 The initial discharge specific capacity is more than 1.6 times that of commercial graphite. Especially at 5.0 A g. -1 At high current density, the discharge specific capacity after 100 cycles is 2.5 to 10.7 times that of commercial graphite batteries, and it also exhibits good cycle stability. This demonstrates that the graphite / nickel oxide / nickel material prepared in this invention is an ideal anode material for lithium-ion batteries with broad application prospects.
[0014] The beneficial effects of this invention are: the process of this invention is simple, and a novel graphite / nickel oxide / nickel lithium-ion battery anode material with high rate and long cycle performance can be prepared by simply calcining a mixture of graphite and nickel acetylacetonate in air. This anode material has excellent discharge specific capacity, especially when charged and discharged at high rates, its performance is even better. Attached Figure Description
[0015] Figure 1 The XRD patterns of commercial graphite (o) and the prepared graphite / nickel oxide / nickel (a) material in Example 1 of the present invention are shown. Figure 2The first charge-discharge diagrams of a half-cell (o) assembled using commercial graphite and a half-cell (a) assembled using the prepared graphite / nickel oxide / nickel in Embodiment 1 of the present invention are shown. Figure 3 In Example 1 of the present invention, a half-cell (o) assembled using commercial graphite and a half-cell (a) assembled using the prepared graphite / nickel oxide / nickel were compared at 5.0 A g. -1 A cyclic diagram showing 100 charge-discharge cycles under the given current; Figure 4 In Example 1 of the present invention, a half-cell (o) assembled using commercial graphite and a half-cell (a) assembled using the prepared graphite / nickel oxide / nickel were compared at 10.0 A g. -1 A diagram showing 500 charge-discharge cycles under ultra-high current. Detailed Implementation
[0016] The following examples are used to illustrate the present invention.
[0017] Example 1 Weigh 0.500 g of graphite and 2.500 g of nickel acetylacetone, making the mass ratio of graphite to nickel acetylacetone 1:5. Grind the mixture of graphite and nickel acetylacetone thoroughly in an agate mortar for 15 min to obtain a mixture. Then, place the mixture in a muffle furnace and calcine it at 600°C for 2 h in air atmosphere to obtain the product sample, which is designated as sample a. For comparison, the commercial graphite material is designated as sample o.
[0018] Sample a, PVDF, and acetylene black were weighed separately and placed in an agate mortar, with the mass ratio of sample a, PVDF, and acetylene black controlled at 8:1:1. The mixture was ground thoroughly for 10 min. Then, N-methylpyrrolidone (NMP) was added dropwise while stirring to form a paste. This paste was then evenly coated onto a commercial Cu foil current collector. The coated current collector was placed in a vacuum drying oven and dried at 120°C for 6 h. After naturally cooling to room temperature, it was removed and cut into several electrode sheets with a diameter of 1.2 cm using a shear, thus obtaining electrode a. Replacing sample a with commercial graphite, and preparing a graphite electrode with all other conditions unchanged, is denoted as electrode o. Finally, using the prepared electrode a as the positive electrode, the lithium sheet as the negative electrode, a Celgard 2400 microporous polypropylene membrane as the separator, 1 mol / L LiPF6 dissolved in an organic solvent as the electrolyte, and a CR2430 button cell casing as the battery casing, a half-cell was assembled in an argon-filled glove box, denoted as battery a. Electrode a was then replaced with electrode o, and following the same steps, a half-cell was assembled, denoted as battery o.
[0019] See Figure 1. Figure 1 XRD patterns of graphite / nickel oxide / nickel (a) and commercial graphite (o) are shown, along with standard XRD patterns of graphite, nickel oxide, and nickel. The test results indicate the presence of characteristic diffraction peaks for graphite, nickel oxide (NiO), and nickel (Ni) in sample a. This suggests that the mixture of nickel acetylacetone and graphite, after high-temperature calcination, forms a graphite / nickel oxide / nickel composite material. Samples o and a exhibit diffraction peaks at 26.7° and 54.7°, respectively, which belong to the (002) and (004) crystal planes of graphite C (JCPDS, No. 12-0212). In addition to the diffraction peaks belonging to graphite carbon materials, characteristic diffraction peaks belonging to NiO and Ni are clearly displayed, with diffraction peaks at 2θ of 37.2°, 43.3°, 62.8°, and 75.4°, which correspond to the (111), (200), (220), and (311) crystal planes of NiO (JCPDS, No. 73-1519), respectively. The diffraction peaks at 2θ of 44.4°, 51.8°, and 76.3° correspond to the (111), (200), and (220) crystal planes of elemental nickel Ni (JCPDS, No. 04-0850), respectively. Literature review shows that there are no reports, either domestically or internationally, on the preparation of composite materials containing graphite, nickel oxide, and nickel by calcining a mixture of graphite and nickel acetylacetone.
[0020] See Figure 2 . Figure 2 For half-cell (o) and half-cell (a) at 0.2 A g -1 The initial charge-discharge curves at current density are shown. It can be seen that the initial discharge specific capacity of batteries o and a is 333.4 mAh g, respectively. -1 650.3 mAh g -1 It can be seen that the discharge specific capacity of battery a is 2.0 times that of battery o (commercial graphite), which indicates that the mixture of calcined graphite and nickel acetylacetonate can significantly improve the initial discharge specific capacity of commercial graphite.
[0021] See Figure 3 . Figure 3 For batteries O and A in 5.0 A g -1 The graph shows the charge-discharge cycle times for the next 100 cycles. As can be seen from the graph, the two batteries perform well at 5.0 A g. -1 Both showed good cycle stability. The discharge specific capacity of battery o at the first and 100th cycles was 26.4 mA hg. -1 and 16.7 mA hg -1 The capacity retention rate was 63.2%; the discharge specific capacity of battery a at the first and 100th cycles was 168.2 mAh g, respectively. -1 and 177.9 mAh g-1 As the cycle continues, the material gradually activates, and the capacity continues to increase. Specifically, at 5.0 Ag... -1 After 100 cycles, the specific capacity of the newly prepared anode material is 10.7 times that of commercial graphite, showing a significant capacity improvement.
[0022] See Figure 4 . Figure 4 For batteries O and A in 10.0 A g -1 The graph shows the results after 500 charge-discharge cycles. As can be seen from the graph, the discharge specific capacity of battery o remains at 5.6 mAh g after 500 cycles. -1 Battery A's capacity gradually increased to a maximum of 63.9 mAh g before 100 cycles. -1 It has 11.4 times the capacity of battery O at the same number of cycles; its discharge specific capacity after 500 cycles is 30.6 mAh g. -1 That is, at 10.0 Ag -1 After 500 cycles, the specific capacity of the newly prepared anode material was still 5.5 times that of commercial graphite. This indicates that, compared to commercial graphite, the novel anode material exhibits superior performance in high-rate, long-cycle conditions, which is of great significance for the research and development of high-rate and power lithium-ion batteries.
[0023] Example 2 0.500 g of graphite and 1.500 g of nickel acetylacetone were weighed to a mass ratio of 1:3. The mixture was then thoroughly ground in an agate mortar for 15 min to obtain a final product. This final product was then calcined in a muffle furnace at 600°C for 2 h in air to obtain sample a. For comparison, a commercial graphite material was named sample o. A half-cell was assembled according to the method in Example 1, and its electrochemical performance was tested. The results showed that at 0.2 A g… -1 The initial discharge specific capacity of battery a is 610 mAh g -1 It is 1.8 times that of battery o. At 5.0 A g -1 After 100 cycles, the discharge specific capacity of battery a is 65 mAh g. -1 It is 3.8 times that of battery O. At 10.0 A g -1 After 500 cycles, the discharge specific capacity of battery a is 21 mAh g. -1 It is 3.5 times that of battery o.
[0024] Example 3 0.300 g of graphite and 2.100 g of nickel acetylacetone were weighed, making the mass ratio of graphite to nickel acetylacetone 1:7. The mixture was then thoroughly ground in an agate mortar for 15 min to obtain a final product. This final product was then placed in a muffle furnace and calcined at 600°C for 2 h in air to obtain sample a. For comparison, a commercial graphite material was named sample o. A half-cell was assembled according to the method in Example 1, and its electrochemical performance was tested. The results showed that at 0.2 A g… -1 The initial discharge specific capacity of battery a is 581 mAh g. -1 It is 1.7 times that of battery o. At 5.0 A g -1 After 100 cycles, the discharge specific capacity of battery a is 43 mAh g. -1 It is 2.5 times that of battery O. At 10.0 A g -1 After 500 cycles, the discharge specific capacity of battery a is 11 mAh g. -1 It is 1.6 times that of battery o.
[0025] Example 4 0.500 g of graphite and 2.500 g of nickel acetylacetone were weighed, making the mass ratio of graphite to nickel acetylacetone 1:5. The mixture was then thoroughly ground in an agate mortar for 10 min to obtain a final product. This final product was then placed in a muffle furnace and calcined at 500°C for 3 h in air to obtain the final product sample, designated as sample a. For comparison, a commercial graphite material was designated as sample o. A half-cell was assembled according to the method in Example 1, and its electrochemical performance was tested. The results showed that at 0.2 A g… -1 The initial discharge specific capacity of battery a is 598mAh g. -1 It is 1.8 times that of battery o. At 5.0 A g -1 After 100 cycles, the discharge specific capacity of battery a is 76 mAh g. -1 It is 4.5 times that of battery O. At 10.0 A g -1 After 500 cycles, the discharge specific capacity of battery a is 23 mAh g. -1 It is 3.8 times that of battery o.
[0026] Example 5 0.500 g of graphite and 2.500 g of nickel acetylacetone were weighed, making the mass ratio of graphite to nickel acetylacetone 1:5. The mixture was then thoroughly ground in an agate mortar for 20 min to obtain a final product. This final product was then placed in a muffle furnace and calcined at 700°C for 1 h in air to obtain the final product sample, designated as sample a. For comparison, a commercial graphite material was designated as sample o. A half-cell was assembled according to the method in Example 1, and its electrochemical performance was tested. The results showed that at 0.2 A g… -1 The initial discharge specific capacity of battery a is 571 mAh g. -1 It is 1.7 times that of battery o. At 5.0 A g -1 After 100 cycles, the discharge specific capacity of battery a is 50 mAh g. -1 It is 2.9 times that of battery o. At 10.0 A g -1 After 500 cycles, the discharge specific capacity of battery a is 13 mAh g. -1 It is 2.2 times that of battery o. Example 6 0.500 g of graphite and 1.500 g of nickel acetylacetone were weighed to make a mass ratio of graphite to nickel acetylacetone of 1:3. The mixture was then thoroughly ground in an agate mortar for 20 min to obtain a final product. This final product was then placed in a muffle furnace and calcined at 500°C for 3 h in air to obtain the final product sample, designated as sample a. For comparison, a commercial graphite material was designated as sample o. A half-cell was assembled according to the method in Example 1, and its electrochemical performance was tested. The results showed that at 0.2 A g… -1 The initial discharge specific capacity of battery a is 544 mAh g. -1 It is 1.6 times that of battery o. At 5.0 A g -1 After 100 cycles, the discharge specific capacity of battery a is 67 mAh g. -1 It is 3.9 times that of battery O. At 10.0 A g -1 After 500 cycles, the discharge specific capacity of battery a is 17 mAh g. -1 It is 2.8 times that of battery o.
Claims
1. A method for preparing a lithium-ion battery anode material, characterized in that, Includes the following steps: (1) Preparation of materials Graphite; Nickel acetylacetonate Ni(acac)2; Acetylene black; Polyvinylidene fluoride (PVDF); N-methylpyrrolidone (NMP); Celgard 2400 microporous polypropylene membrane; CR2430 button battery casing; (2) Material preparation Graphite and nickel acetylacetone were weighed out in a mass ratio of 1~2:3~7, and the two were mixed to obtain a mixture. The mixture was then placed in a muffle furnace and calcined at 500℃~700℃ for 1 h~3 h in an air atmosphere to obtain a product containing graphite, nickel oxide and nickel, named sample a. (3) Electrode preparation and battery assembly For comparison, the commercial graphite was named Sample O; Sample a, PVDF, and acetylene black were weighed separately and placed in an agate mortar. The mass ratio of sample a, PVDF, and acetylene black was controlled to be 8~9:1~1.5:1~1.
5. The mixture of the three was thoroughly ground in the agate mortar for 10~20 min. Then, N-methylpyrrolidone (NMP) was added dropwise while stirring to form a paste. The resulting paste was then evenly coated onto a commercial copper foil current collector. The current collector coated with the paste was then placed in a vacuum drying oven and dried at 100℃~120℃ for 4 h~8 h. After naturally cooling to room temperature, it was removed and cut into several electrode sheets with a diameter of 1 cm~2 cm using a shearing tool, thus obtaining electrode a. The graphite electrode prepared by replacing sample a with commercial graphite while keeping everything else unchanged is denoted as electrode o. Using the prepared electrode a as the positive electrode, a lithium sheet as the negative electrode, a Celgard 2400 microporous polypropylene membrane as the separator, 1 mol / L LiPF6 dissolved in an organic solvent as the electrolyte, and a CR2430 button cell casing as the battery casing, a half-cell was assembled in an argon-filled glove box, denoted as battery a. Electrode a was replaced with electrode o, and following the same steps, a half-cell was assembled under the same conditions, denoted as battery o. The charge and discharge experiments of the half-cell were conducted on a high-precision battery charge and discharge tester.
2. The method for preparing a lithium-ion battery negative electrode material according to claim 1, characterized in that, In step (2), the mass ratio of graphite to nickel acetylacetone is 1:
5.
3. The method for preparing a lithium-ion battery negative electrode material according to claim 1, characterized in that, In step (2), the calcination temperature of the graphite and nickel acetylacetone mixture in the muffle furnace is 600℃.
4. The method for preparing a lithium-ion battery negative electrode material according to claim 3, characterized in that, In step (2), the graphite and nickel acetylacetone mixture is calcined in a muffle furnace for 2 hours.
5. The method for preparing a lithium-ion battery negative electrode material according to claim 1, characterized in that, The mass ratio of sample a, PVDF and acetylene black prepared in step (3) is 8:1:
1.
6. The method for preparing a lithium-ion battery negative electrode material according to claim 1, characterized in that, The grinding time for sample a, PVDF and acetylene black prepared in step (3) is 15 min.
7. The method for preparing a lithium-ion battery negative electrode material according to claim 1, characterized in that, In step (3), the temperature in the vacuum drying oven during electrode preparation is 120°C.
8. The method for preparing a lithium-ion battery negative electrode material according to claim 7, characterized in that, In step (3), the electrode preparation process involves drying in a vacuum drying oven for 6 hours.
Citation Information
Patent Citations
Ferroferric oxide / graphite lithium ion battery anode material and preparation method for ferroferric oxide / graphite lithium ion battery anode material
CN102610809A
Preparation method of N-doped 3D graphene / graphite lithium ion battery negative material
CN104882608A
Pearl cotton shaped nickel oxide lithium battery negative electrode material and preparation method thereof
CN107170983A
Preparation process of high-purity nano nickel oxide
CN120440975A
Modified graphite as well as preparation method and application thereof
CN122202234A